The Development of SOLMAT (Solution Math) Application on Basic Mathematics Material for Improve Learning Outcomes - Toyo Wiyatno; Wahyu Hidayat (IKIP Siliwangi, 2023)
Only 28% of students in Indonesia are capable of interpreting problems into mathematical models, due to their lack of understanding of basic mathematical concepts. The purpose of stimulating and guided training is to provide students with a good understanding of problem solving in mathematics. Based on this concept, the purpose of developing the Basic Mathematical Solution Application (SOLMATDAS) is to provide understanding to students with guided training using android as the medium. Media development follows the 4D methodology (Define, Design, Develop, Disseminate), with media and ICT validation by each expert and media effectiveness by learning participants. from the results of the validation test, the percentage of learning expert validation was 90% and ICT expert validation was 90.2%, so the media can be categorized as very valid and can be used as a learning media, whereas after dissemination and testing the effectiveness of the media in obtaining pretest and posttest scores it was carried out by teacher to students in one class. The results of processing the pre-test and post-test statistics obtained a significance value of 0.038, because the significance is less than 0.05 which means there are differences in learning outcomes using SOLMAT and direct learning. From these results it can be concluded that the use of the SOLMAT application can assist in advanced mathematics learning activities which requires an understanding of basic mathematical concepts.